Identification of Mosquito Bloodmeals Using Polymerase Chain Reaction (PCR) With Order-Specific Primers. Issue 2 (6th October 2014) - Ngo, Kiet A.; Kramer, Laura D.
Abstract : A polymerase chain reaction (PCR) protocol was developed to identify host bloodmeals from mosquitoes. Primers for the cytochrome b gene were designed to distinguish between mammalian and avian bloodmeals and further differentiate among four avian orders: passeriformes, falconiformes, columbiformes, and galliformes. The assay was validated by testing tissues from 18 species of passeriformes, three species of falconiformes, three species of columbiformes, and two species of galliformes. American crows were distinguished from other passeriformes by restriction enzyme digestion. Host bloodmeals from engorged mosquitoes collected in New York State were identified to avian order level. PCR was able to detect the mosquito bloodmeal for up to 3 d after feeding on a quail. Significantly, these studies use order-specific primers in a single PCR test to identify mosquito bloodmeals.